Efeito do diabete moderado na matriz extravelular e no músculo estriado uretral em ratas prenhez - Piculo, Fernanda [UNESP] (2013)
The maternal diabetes constitutes an unfavorable environment for the fetal-placental and embryonic development. It is an important repercussion in modern obstetrics, since it´s associated to an increased risk of neonatal and maternal morbidity and it still is a significant medical challenge. The worldwide diabetes increased level, the increase of diabetes type 2 in reproductive age women and the crossed generation of the intrauterine programation from diabetes type 2 are the bases for the growing interest in the utilization of diabetics experimental samples, with the aim to adquire knowledge about the mechanisms that induce the development alterations at the gestational diabetes. Several studies have showed the benefits of the diabetes prevention, with interventions in the life style, metabolic improvement and control of the cardiovascular risk factor to substantially avoid this disease devastating complications. Despite these findings, the recent revolution in the scientific knowledge and the infinites new therapies for diabetes, there is still a large gap between what was learned through the researches and what is really done in the public, clinical and communitary health. The negative economic impact of this complacency in the people, families and national economies is alarming. It is expected that translational research in diabetes and pregnancy binomial are implemented in centers of excellence, in both basic and applied research, and complemented by multicenter clinical studies, conducted in a pragmatic way to increase the level of scientific evidence with more reliable diagnostic and propaedeutic resources